Implementation of Distance Learning Based on Problem-Based Learning to Increase Critical Thinking Skills - Kuntari, Septi; Setiawan, Rizki; Lindawati, Yustika Irfani (KnE Social Sciences, 2021)
Problem-based learning (PBL) is a learning model that requires the active participation of each individual, who in the learning process all help to determine the subject matter. The PBL model can foster students’ critical thinking skills through solving various real-world problems found in the environment where they live. This research aimed to improve students’ critical thinking skills through PBL-based online learning. Quantitative experimental methods were used. A one group pretest-posttest design was employed: a preliminary test (pretest) was carried out, followed by the treatment, and finally the final test (posttest). There were two experimental groups: A and B. The results showed that students’ critical thinking skills increased in both group A and group B and this change was significant, as measured through a t-test (p < 0.05 in both groups). Keywords: distance learning; problem-based learning; critical thinking skills; sociology of education.